Analysis of surface contamination of severe acute respiratory syndrome coronavirus 2 in a health-care setting in the context of the coronavirus disease-2019 pandemic - Amrish Kohli; Kamna Singh; Yangchen Dolma (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Hospital-onset coronavirus disease-2019 (COVID-19) infection has been reported and is probably linked to ineffective implementation of infection prevention and control measures. Contaminated surfaces and air are considered a key part of the transmission dynamics of severe acute respiratory syndrome, Middle East respiratory syndrome, influenza, and other organisms in hospitals. This study aimed to assess the extent and persistence of surface contamination with COVID-19. MATERIALS AND METHODS: It was a hospital-based cross-sectional study conducted for a period for 2 weeks from December 03, 2020, to December 16, 2020, in Kathua district of J and K, India. The environmental samples were taken from the patient care area that included COVID isolation ward and intensive care unit (ICU) as per the guidelines of WHO Protocol "Surface sampling of COVID-19: A practical "how to" protocol for health care and public health professionals after seeking copyright permission from the WHO. Universal standard precautions were strictly followed. Descriptive analysis was done using the MS-Excel and expressed in numbers and percentages. RESULTS: A total of 140 surface samples were taken, 70 each from the COVID ICU and isolation ward. The results of ten samples from the ICU turned out to be positive and 20 samples were positive from the isolation ward. Eleven (78.6%) out of the 14 samples taken from the corners of the ICU and isolation ward were found to be positive. CONCLUSION: Our study revealed surface contamination in the hospital setting both in COVID ICU and isolation ward particularly from the corners of the COVID ICU and isolation ward followed by the samples taken from the linen. Strict adherence to COVID appropriate behavior, increased frequency of disinfection in high-risk areas, and sensitization of the staff are mandatory to minimize the infection risk.